Nutrigenomics: A perio-nutrition interrelationship - Nitin Tomar; Chandni Gupta; Mayur Kaushik; Amit Wadhawan (Wolters Kluwer Medknow Publications, 2017)
Periodontitis results from the loss of a delicate balance between microbial virulence factors and a proportionate host response. Nutrition may be important in redressing the balance between microbial challenge and the host response because it has been implicated in a number of inflammatory diseases and conditions, including type II diabetes mellitus, cardiovascular diseases, rheumatoid arthritis, and inflammatory bowel disease, all of which have also been associated with periodontal diseases. Nutrigenomics is concerned with the impact of dietary components on the genome, proteome (the sum total of all proteins), and metabolites (the sum of all metabolites). This article reviews the evidence for nutritional impact on periodontitis.